Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. SUCOFINDO Cabang Jambi - Rozi, A.; Budianto, Achyat; Evrina, Evrina; Muarif, M Alfin (Politeknik Negeri Ambon, 2024)
This research scrutinized the impact of Work Discipline and Work Motivation on Employee Performance at PT. Sucofindo, Jambi Branch. Employing a quantitative approach, the investigation was conducted on 62 workers from PT. Sucofindo, Jambi Branch, was chosen as the population and sample, and data gathering was executed via questionnaire dissemination. The sample selection was performed utilizing a saturated sampling methodology. At the same time, data analysis comprised descriptive examination, multiple linear regression, and simultaneous, partial evaluations of the determination coefficient. Employee Performance is favorably and considerably influenced by Work Discipline (X1), evidenced by a significance index of 0.000, below 0.05, and a derived t-statistic of 6.280, surpassing the threshold t-table statistic of 1.671. Similarly, Employee Performance is positively and significantly affected by Work Motivation (X2), as demonstrated by a significance index of 0.000, lower than 0.05, and a derived t-statistic of 6.841, more significant than the threshold t-table statistic of 1.671. These factors, Work Discipline and Work Motivation, are instrumental in enhancing Employee Performance. In summation, it has been discerned that Employee Performance is profoundly impacted by both Work Discipline (encompassing time scheduling, structuring, conduct, and additional protocols) and Work Motivation, which inherently pertains to skill diversity, task identification, task importance, independence, and responses. Employee Performance is elevated through heightened Work Discipline and Work Motivation.